The Role of Smart Citizens in Building a Smart Bangladesh: Challenges and the Way Forward - Hasan, Nazmul; Mostafa, Md. Golam (Khwopa Journal, 2024)
Bangladesh's government aims to achieve smart country and sustainable city status by 2041 through the vital topic of smart Bangladesh. This study investigated the crucial role of citizens in the journey towards building a smart Bangladesh, with a focus on analyzing factors influencing citizen participation and addressing challenges to realize the Vision of 2041. Applying a quantitative approach based on positivism philosophy, the research adopts an exploratory research design. Close-ended questionnaires are a primary data collection method that are administered through a variety of channels, including email, Google Forms, and social media platforms. The study covered all eight administrative divisions (Dhaka, Chittagong, Rajshahi, Barishal, Khulna, Rangpur, Sylhet, and Mymensingh) of Bangladesh, with a total of 250 respondents randomly chosen from the general population. Findings from this study are expected to shed light on the factors influencing active citizen engagement and offer insights into overcoming challenges on the pathway to achieving the bold Vision of 2041 for a Smart Bangladesh.